Counter-terrorism narrative strategies - Maan, Ajit K. (University Press Of America, 2015)
Counter-Terrorism makes a connection, unique to terrorism studies, between the mechanisms of colonizing narratives and psychological warfare aimed at recruitment. There is an urgent need to understand the narrative tactics of terrorist recruitment and an equal if not greater need to destabilize and exploit the weaknesses of those narratives.